Why I do what I do: global curators speak - Ayas, Defne 1976- (Sternberg Press, 2024)
"For this fourth volume of the series Thoughts on Curating, twenty renowned curators and collectives from across the globe write about a single exhibition or curatorial project they created that transformed their thinking and the way they have curated ever since. Their innovations, practical considerations, and ways of grappling with the most urgent issues of the day offer a unique handbook of curatorial ideas--rational and whimsical, poetic and political--and serve as a fascinating record of exhibition-making in the twenty-first century"-- Publisher's website
Keywords: Kurator -- Museumskunde; Curatorship